(untitled) (Research, Society and Development, 2021)
Objective: to describe nurses’ conceptions about safe care for women during pregnancy and childbirth. Method: this is a qualitative, descriptive study, carried out in a public maternity hospital in the city of Rio de Janeiro. Nurses working in prenatal care and in assisting normal birth were interviewed. Thematic content analysis was used. Results: 11 nurses participated in the study. The content analysis gave rise to two thematic categories, called “Safe obstetric care in the nurses’ conception” and “The promotion of safe care for nurses”. Nurses consider that the security of obstetric care is obtained through the use of protocols and technical standards recommended by the Ministry of Health, seeking to provide assistance free of errors and damages, without unnecessary interventions and through humanized care, with trained and qualified professionals. appropriate infrastructure. The promotion of safety occurs when there is the prevention of risks, the valorization of the role of women and respect for the physiology of childbirth, through individualized assistance. Conclusion: in the nurses’ conceptions, safe assistance to women during pregnancy and childbirth, is when there is a humanized and individualized care, without unnecessary interventions, through adherence to technical recommendations, with trained professionals and an adequate infrastructure, in order to minimize errors and damages. Nurses highlight the importance of encouraging women’s autonomy, through a welcoming and trained team, which provides the necessary information and guidance, contributing to women’s safety.